Metode Analisis Cemaran Mikroba pada Makanan : Review Artikel - Aditia Putra Tama; Vina Luthfiana Hasna; Khamairah Azzahrawaani Hermawan; Marsah Rahmawati Utami; Lina Nurfadhila (Journal of Pharmaceutical and Sciences, 2023)
Food is one of the important things in the sustainability of human life. The main function of food for humans is to meet the nutritional needs of the body, where these nutrients must be met according to gender, age, daily physical activity, and body weight. As the main and basic function of food itself, in order to be a good source of nutrients and energy, of course, the food must be ensured to be safe, clean, does not contain harmful food-enhancing ingredients, and is free from sources of disease. The source of this disease can arise from food that has been contaminated, one of which is food contaminated with microbial contamination. This article aims to inform the analysis of microbial contamination methods in various foods. The method used in writing this article review is to search for several references in the form of scientific journals or scientific articles from research with the keyword microbial contamination analysis.